2013
DOI: 10.2106/jbjs.l.00077
|View full text |Cite
|
Sign up to set email alerts
|

Primary Osteoarthritis of the Hip: A Genetic Disease Caused by European Genetic Variants

Abstract: Primary osteoarthritis of the hip is a separate phenotype that occurs at a rate of 3% to 6% in the populations of the world with European ancestry. In all non-European populations, there is a consistent rarity of primary osteoarthritis that suggests a different etiology for these few patients. Family, sibling, and twin studies prove primary osteoarthritis to be a genetic disease with a 50% heritability caused by European genetic variants. The genetic basis is reinforced by the lower rate of primary osteoarthri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 58 publications
3
18
0
Order By: Relevance
“…Previous studies have suggested a familial predisposition to hip arthritis and total hip arthroplasty [3][4][5][6][7][8][9][10]. Our data further support the findings of a heritable predisposition to severe osteoarthritis leading to total hip arthroplasty.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Previous studies have suggested a familial predisposition to hip arthritis and total hip arthroplasty [3][4][5][6][7][8][9][10]. Our data further support the findings of a heritable predisposition to severe osteoarthritis leading to total hip arthroplasty.…”
Section: Discussionsupporting
confidence: 91%
“…In a recent review of the literature, Hoaglund [6] summarized family, sibling, and twin studies in which primary osteoarthritis was found to be a genetic disease with a 50% heritability caused by European genetic variants. The genetic basis of this finding was reinforced by the lower rate of primary osteoarthritis in American minorities consistent with their degree of European gene admixture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another explanation could be the similar prevalence of hip OA in Australasia and Europe, as demonstrated in the Global Burden of Disease Study (prevalence for females 0.9% in Australasia versus 1.2% in Europe; prevalence for males 0.7% in Australasia versus 0.8–0.9% in Europe) . Hip OA is known to have a strong genetic component and is particularly linked to European genetic variants . This linkage is relevant for the Scandinavian countries as well as for Australia, which has a long history of European migration (68% of Australians report at least 1 type of European ancestry) .…”
Section: Discussionmentioning
confidence: 81%
“…He specialized in population-based studies, both in the United States and elsewhere. He pursued this interest into his retirement, publishing an already-classic review article [1] spanning epidemiology and genetics at the age of 82 (Fig. 2).…”
Section: F Ranklin T Hoaglund MDmentioning
confidence: 99%